Prediction method for fused CMAS penetration behavior of zirconia-based thermal barrier coating
By applying scanning electron microscope, MATLAB and COMSOL Multiphysics technical means on zirconia-based thermal barrier coating, a method for predicting the penetration behavior of CMAS in thermal barrier coating was established, which solved the problem that the existing technology could not predict the penetration behavior of CMAS, and achieved effective evaluation and optimization of coating performance.
Patent Information
- Application Number
- CN202411581310.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-25
AI Technical Summary
The prior art cannot effectively predict the CMAS penetration behavior of thermal barrier coatings, affecting the corrosion resistance and life of the coating.
By preparing zirconia-based thermal barrier coating, microstructure images were obtained using scanning electron microscope, combined with MATLAB image processing and COMSOL Multiphysics simulation, constitutive equations reflecting the internal CMAS penetration behavior of the coating were established to achieve non-destructive detection and prediction.
Accurate simulation and prediction of the permeability behavior of thermal barrier coatings is achieved, providing guidance on optimizing the coating microstructure to improve anti-CMAS permeability.
Smart Images

Figure CN119514028A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of thermal barrier coatings for aircraft engines, and more specifically to a method for predicting the penetration behavior of molten CMAS of a zirconium oxide-based thermal barrier coating. Background Art
[0002] Thermal barrier coatings (TBCs) are a typical protective coating composed of refractory oxide ceramics. They are prepared on the surface of high-temperature alloy hot-end components in aircraft engines. They can effectively isolate high-temperature combustion gases from metal hot-end components and reduce the surface temperature of these metal components so that they can serve above their melting point, thereby improving the thermal efficiency of aircraft engines.
[0003] Molten silicate, namely calcium-magnesium-alumino-silicate (CMAS), usually comes from sand, volcanic ash or fuel residue in the air, with a melting point of 1463-1533K, and is a common corrosive material in aircraft engines. During service, CMAS particles will enter the engine from the air. When the ambient temperature exceeds its melting point, they will melt and adhere to the surface of the high-temperature thermal barrier coating, and easily penetrate into the pores of the coating. During the cooling process, CMAS solidifies, which increases the in-plane elastic modulus and stiffness of the coating. As the penetration depth of CMAS increases, the strain energy release rate of the CMAS-penetrated coating increases, making the coating easier to delaminate and peel. On the other hand, as CMAS penetration proceeds, the porosity decrease caused by CMAS filling gradually intensifies, further reducing the strain tolerance and thermal insulation performance of the thermal barrier coating. Therefore, CMAS penetration is a key factor affecting the failure of thermal barrier coatings.
[0004] At present, a variety of thermal barrier coating materials and coating microstructure design methods that are resistant to CMAS corrosion have been developed. For example, a Ti2AlC mixed phase protective layer is applied on the surface of the thermal barrier coating using the slurry method to effectively prevent the penetration of CMAS in the coating; a micro-nano dual-scale structure with cluster-like protrusions is developed on the top of the ceramic coating by the solution precursor plasma spraying method, which effectively hinders the adhesion of molten CMAS on the surface of the thermal barrier coating and alleviates the occurrence of CMAS corrosion.
[0005] Although these existing technologies can effectively improve the CMAS penetration resistance of thermal barrier coating systems, there are currently no relevant technical means to predict the CMAS penetration behavior of thermal barrier coatings, and it is impossible to judge and predict the CMAS penetration resistance of the coating based on the microstructure of the prepared coating. Therefore, it is urgent to establish a non-destructive prediction method for CMAS corrosion behavior, which is of great significance for the life evaluation of thermal barrier coating systems, material composition and coating microstructure optimization. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention aims to provide a method for predicting the molten CMAS penetration behavior of zirconia-based thermal barrier coatings. Through this method, the resistance of the coating to molten CMAS penetration can be predicted according to the microstructural characteristics of the coating, non-destructive testing of the CMAS penetration performance of the thermal barrier coating can be achieved, and further guidance can be provided for the microstructural design of the thermal barrier coating that is resistant to CMAS penetration.
[0007] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0008] The present invention provides a method for predicting the penetration behavior of molten CMAS of a zirconium oxide-based thermal barrier coating, comprising the following steps:
[0009] S1: Prepare thermal barrier coating and obtain microstructure image of thermal barrier coating using scanning electron microscope;
[0010] S2: Use MATLAB image processing to build a numerical model based on the microstructure image of the thermal barrier coating;
[0011] S3: Mesh the established numerical model in COMSOL Multiphysics;
[0012] S4: Based on the Carman-Kozeny model and Darcy's law, a constitutive equation reflecting the relationship between the molten CMAS penetration time, porosity, penetration path complexity and penetration contact angle inside the coating is established;
[0013] S5: Select the physical field interface, bring the constitutive equation into COMSOL Multiphysics, set the parameters and boundary conditions for calculation;
[0014] S6: Post-process the calculation results to obtain the CMAS penetration behavior inside the microstructure of the thermal barrier coating.
[0015] Preferably, in step S1, the method for preparing the thermal barrier coating is: plasma spraying, electron beam physical vapor deposition or plasma spraying-physical vapor deposition;
[0016] Preferably, the thermal barrier coating is a zirconium oxide-based thermal barrier coating; the thermal barrier coating component is 8 wt% Y2O3-ZrO2.
[0017] Preferably, in step S2, MATLAB image processing is used to determine the threshold of the microstructure image of the thermal barrier coating through a gray threshold function, the microstructure image of the thermal barrier coating is converted into a threshold-based binary image using the im2bw function, and the noise in the binary image is eliminated using the imerode and imexpate functions, and finally the processed binary image is converted into a vector image to complete the modeling.
[0018] Preferably, in step S3, the physical field in COMSOL Multiphysics is used to control the grid, the unit type is a free triangle grid, the maximum grid size is 0.2 μm, the minimum grid size is 0.004 μm, and an adaptive grid is used to simulate the CMAS penetration process.
[0019] Preferably, the specific method of step S4 is:
[0020] (1) Based on Darcy's law, a relationship between the penetration time of molten CMAS is established;
[0021] (2) establishing a relationship for the effective radius of the CMAS permeable pore based on the numerical model established in step S3;
[0022] (3) Based on the Carman-Kozeny model, the relationship between CMAS permeability and the internal microstructure of thermal barrier coatings is established;
[0023] (4) Combining steps (1)-(3), a constitutive equation for the relationship between the molten CMAS penetration time, porosity, penetration path complexity and penetration contact angle inside the coating is established.
[0024] Preferably, the relationship between the penetration time of molten CMAS is:
[0025]
[0026] Wherein, t is the penetration time of molten CMAS, s; r is the effective radius of the CMAS penetration pore, μm; μ is the viscosity of molten CMAS, Pa·s; x is the model height, μm; σ is the surface tension of molten CMAS, N / m; θ is the contact angle between molten CMAS and the model, °; k is the permeability of CMAS in the model, μm 2 .
[0027] Preferably, the relationship between the effective radius of the CMAS permeable pore is:
[0028]
[0029] Where b is the equivalent radius of the model, μm; a is the equivalent radius of the unmelted particles in the model, μm.
[0030] Preferably, the relationship between the CMAS permeability and the internal microstructure of the thermal barrier coating is:
[0031]
[0032] Where k is the CMAS permeability in the model, μm 2 ; φ is the porosity, %; τ is the geometric shape factor, which is used to describe the complexity of the penetration path, which is equal to the effective area of the penetration pores / the effective area of the unmelted particles.
[0033] Preferably, the constitutive equation for the relationship between the molten CMAS penetration time, porosity, penetration path complexity, and penetration contact angle inside the coating is:
[0034]
[0035] Preferably, in step S5, COMSOL simulation selects phase field and laminar flow interfaces, the model boundary is fixed, the initial CMAS concentration of the upper surface is 1, the initial CMAS concentration of the lower surface is 0, and the CMAS concentration of all outer surfaces of the model is 0; a transient study is set, and the output step size is 0.01 seconds;
[0036] In step S6, the CMAS penetration behavior includes: the penetration area and penetration depth changes of the molten CMAS inside the model at different times.
[0037] The technical solution of the present invention achieves the following beneficial technical effects:
[0038] 1. The present invention provides a method for predicting the penetration behavior of molten CMAS inside a thermal barrier coating based on its microstructure, which can accurately simulate the CMAS penetration process inside the microstructure of the thermal barrier coating. The method is economical, efficient and non-destructive to the test sample, filling the research gap in the relevant field.
[0039] 2. The method of the present invention can clarify the relationship between the coating microstructure and the CMAS penetration behavior, and provide effective guidance for improving the anti-CMAS penetration performance in the field of thermal barrier coatings by regulating the coating microstructure.
[0040] 3. The technical solution provided by the present invention comprehensively considers the influence of various factors such as porosity, unmelted particles, complexity of penetration path, and penetration contact angle on the penetration behavior of molten CMAS inside thermal barrier coatings, and can be applied to the prediction of CMAS penetration behavior inside the microstructure of thermal barrier coatings prepared by various deposition methods. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 is a flow chart of a method for predicting the penetration behavior of molten CMAS of a thermal barrier coating according to the present invention;
[0042] Figure 2The microstructure of the thermal barrier coating sample and the constructed numerical model in the embodiment of the present invention;
[0043] in, Figure 2 A is a scanning electron microscope image (10 μm) of the thermal barrier coating sample provided in Example 1; Figure 2 B is a scanning electron microscope image (5 μm) of the thermal barrier coating sample provided in Example 1; Figure 2 C is a numerical model constructed based on the microstructural characteristics of the coating in Example 1; Figure 2 D is a scanning electron microscope image (10 μm) of the thermal barrier coating sample provided in Example 2, Figure 2 E is a scanning electron microscope image (5 μm) of the thermal barrier coating sample provided in Example 2, Figure 2 F is a numerical model constructed based on the microstructural characteristics of the coating in Example 2;
[0044] Figure 3 is an image of the numerical model in the embodiment of the present invention after meshing in COMSOL Multiphysics;
[0045] in, Figure 3 A is the image of the numerical model in Example 1 after meshing, Figure 3 B is the image of the numerical model in Example 2 after meshing;
[0046] Figure 4 It is the molten CMAS penetration process inside the coating microstructure obtained by simulation results in the embodiment of the present invention;
[0047] in, Figure 4 A is the molten CMAS penetration process inside the microstructure of the thermal barrier coating sample provided in Example 1 obtained through simulation calculation, Figure 4 B is the molten CMAS penetration process inside the microstructure of the thermal barrier coating sample provided in Example 2 obtained through simulation calculation; the red area is the part where the molten CMAS has penetrated, and the blue area is the part where the molten CMAS has not penetrated;
[0048] Figure 5 is a curve diagram showing the average penetration depth variation of the molten CMAS in the coating microstructure within 3 seconds obtained from the simulation results in the embodiment of the present invention;
[0049] Figure 6 is a scanning electron microscope image (200 μm) of the thermal barrier coating sample in the embodiment of the present invention after the molten CMAS actually penetrated for 1 hour;
[0050] Among them, Figure 6 A shows that the actual penetration depth of the coating sample provided in Example 1 after CMAS penetration for 1 hour is about 220 μm; Figure 6B It can be seen that the actual penetration depth of the coating sample provided in Example 2 after CMAS penetration for 1 hour is about 187 μm. DETAILED DESCRIPTION
[0051] In order to make the purpose, technical scheme and technical effect of the invention of this application clearer, the technical scheme in the embodiment of this application will be clearly and completely described below in conjunction with the drawings in the embodiment of this application. Obviously, the described embodiment is a part of the embodiment of this application, not all the embodiments. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0052] In view of the technical problems existing in the prior art, the present invention provides a method for predicting the penetration behavior of molten CMAS of a zirconium oxide-based thermal barrier coating, comprising the following steps:
[0053] S1: Prepare thermal barrier coating and obtain microstructure image of thermal barrier coating using scanning electron microscope;
[0054] S2: Use MATLAB image processing to build a numerical model based on the microstructure image of the thermal barrier coating;
[0055] S3: Mesh the established numerical model in COMSOL Multiphysics;
[0056] S4: Based on the Carman-Kozeny model and Darcy's law, a constitutive equation reflecting the relationship between the molten CMAS penetration time, porosity, penetration path complexity and penetration contact angle inside the coating is established;
[0057] S5: Select the physical field interface, bring the constitutive equation into COMSOL Multiphysics, set the parameters and boundary conditions for calculation;
[0058] S6: Post-process the calculation results to obtain the CMAS penetration behavior inside the microstructure of the thermal barrier coating.
[0059] Specifically, in step S1, the method for preparing the thermal barrier coating is: plasma spraying, electron beam physical vapor deposition or plasma spraying-physical vapor deposition; a scanning electron microscope is used to capture a microstructure image of the prepared coating to reflect the pores and unmelted particle characteristics inside the coating.
[0060] Specifically, in step S2, MATLAB image processing is used to determine the threshold of the microstructure image of the thermal barrier coating through a gray threshold function, the im2bw function is used to convert the microstructure image of the thermal barrier coating into a threshold-based binary image, and the imerode and imexpate functions are used to eliminate noise in the binary image. Finally, the processed binary image is converted into a vector image to complete the modeling.
[0061] Specifically, in step S3, the physical field in COMSOL Multiphysics is used to control the mesh, the unit type is a free triangle mesh, the maximum mesh size is 0.2 μm, the minimum is 0.004 μm, and an adaptive mesh is used to simulate the CMAS penetration process.
[0062] Specifically, the specific method of step S4 is:
[0063] (1) Based on Darcy's law, a relationship between the penetration time of molten CMAS is established;
[0064] (2) establishing a relationship for the effective radius of the CMAS permeable pore based on the numerical model established in step S3;
[0065] (3) Based on the Carman-Kozeny model, the relationship between CMAS permeability and the internal microstructure of thermal barrier coatings is established;
[0066] (4) Combining steps (1)-(3), a constitutive equation for the relationship between the molten CMAS penetration time, porosity, penetration path complexity and penetration contact angle inside the coating is established.
[0067] Specifically, the relationship between the penetration time of molten CMAS is:
[0068]
[0069] Wherein, t is the penetration time of molten CMAS, s; r is the effective radius of the CMAS penetration pore, μm; μ is the viscosity of molten CMAS, Pa·s; x is the model height, μm; σ is the surface tension of molten CMAS, N / m; θ is the contact angle between molten CMAS and the model, °; k is the permeability of CMAS in the model, μm 2 ;
[0070] Specifically, the relationship between the effective radius of the CMAS permeable pore is:
[0071]
[0072] Where b is the equivalent radius of the model, μm; a is the equivalent radius of the unmelted particles in the model, μm;
[0073] Specifically, the relationship between CMAS permeability and the internal microstructure of thermal barrier coating is:
[0074]
[0075] Where k is the CMAS permeability in the model, μm 2 ; φ is the porosity, %; τ is the geometric shape factor, which is used to describe the complexity of the penetration path, which is equal to the effective area of the penetration pores / the effective area of the unmelted particles;
[0076] Specifically, the constitutive equation for the relationship between the penetration time, porosity, complexity of the penetration path, and the penetration contact angle of the molten CMAS inside the coating is:
[0077]
[0078] Specifically, in step S5, the COMSOL simulation selects the phase field and laminar flow interfaces, the model boundary is fixed, the initial CMAS concentration on the upper surface is 1, the initial CMAS concentration on the lower surface is 0, and the CMAS concentration on all external surfaces of the model is 0; a transient study is set, and the output step size is 0.01 seconds.
[0079] Specifically, in step S6, the CMAS penetration behavior includes: the penetration area and penetration depth changes of the molten CMAS inside the model at different times.
[0080] The following is a detailed description of a method for predicting the molten CMAS permeation behavior of a zirconium oxide-based thermal barrier coating according to the present invention through specific examples.
[0081] Example 1
[0082] like Figure 1 A method for predicting the permeation behavior of molten CMAS of a zirconium oxide-based thermal barrier coating provided by an embodiment of the present invention is shown, comprising the following steps:
[0083] S1: Prepare thermal barrier coatings and summarize the coating microstructure characteristics.
[0084] The step S1 specifically includes:
[0085] (1) The YSZ thermal barrier coating sample was prepared on the surface of the carbon steel substrate after sandblasting roughening by atmospheric plasma spraying. The main spraying parameters were: current 600A, power 40kW, main gas Ar flow rate 35SLPM, H2 flow rate 8SLPM, spraying distance 80mm, spray gun speed 500mm / s, coating composition 8wt% Y2O3-ZrO2, and the obtained YSZ coating thickness was about 900μm.
[0086] (2) The prepared thermal barrier coating samples were cut, mounted and subjected to standard metallographic processing, and then extracted using a scanning electron microscope to obtain the following Figure 2 The microstructural characteristics of the coating shown in AB (including pores and unmelted particles inside the coating).
[0087] S2: Use MATLAB image processing to construct a numerical model based on the microstructural characteristics of the coating.
[0088] The step S2 specifically includes:
[0089] (1) Figure 2 The image (B) showing microstructural details such as pores and unmelted particles in the thermal barrier coating sample was opened in MATLAB software, and the appropriate threshold was determined using the gray threshold function.
[0090] (2) The im2bw function is used to convert the image into a threshold-based binary image, and the imerode and imexpate functions are used to eliminate noise in the binary image.
[0091] (3) Import the processed binary image into CorelDraw software and convert it into a vector image, thereby creating a Figure 2 C shows the numerical model, where the white parts are unmelted particles and the black parts are permeable pores.
[0092] S3: The established numerical model is meshed in COMSOL Multiphysics. Specifically, the physical field control mesh in COMSOL Multiphysics is used, the unit type is free triangle mesh, the maximum mesh size is 0.2μm, and the minimum is 0.004μm. Adaptive mesh is used to simulate the CMAS penetration process. The final result of meshing is as follows: Figure 3 As shown in A.
[0093] S4: Based on the Carman-Kozeny model and combined with Darcy's law for steady-state unidirectional flow of viscous fluid through porous media, a constitutive equation reflecting the relationship between the penetration time, porosity, complexity of the penetration path and the penetration contact angle of the molten CMAS inside the coating is established.
[0094] The step S4 specifically includes:
[0095] (1) For the flow model of viscous fluid through porous media, it is necessary to establish a relationship between the penetration time of molten CMAS based on Darcy's law, as follows:
[0096]
[0097] Wherein, t is the penetration time of molten CMAS, s; r is the effective radius of the CMAS penetration pore, μm; μ is the viscosity of molten CMAS, Pa·s; x is the model height, μm; σ is the surface tension of molten CMAS, N / m; θ is the contact angle between molten CMAS and the model, °; k is the permeability of CMAS in the model, μm 2 .
[0098] (2) Based on the numerical model established in step S3, the effective radius r of the CMAS permeable pore is defined as follows:
[0099]
[0100] Where b is the equivalent radius of the model, μm; a is the equivalent radius of the unmelted particles in the model, μm.
[0101] (3) According to the Carman-Kozeny model, the relationship between the permeability of CMAS and its internal microstructure in the model can be reflected as follows:
[0102]
[0103] Where k is the CMAS permeability in the model, μm 2 ; φ is the porosity, %; τ is the geometric shape factor, which is used to describe the complexity of the penetration path, which is equal to the effective area of the penetration pores / the effective area of the unmelted particles.
[0104] Combining formulas (1)-(3), a constitutive equation reflecting the relationship between the molten CMAS penetration time, porosity, penetration path complexity and penetration contact angle inside the coating is established, as follows:
[0105]
[0106] S5: Select the physical field interface, set the parameters and boundary conditions, and bring the constitutive equation into COMSOL Multiphysics for calculation.
[0107] Specifically, the phase field and laminar flow interfaces in COMSOL were selected; the model contained two phases of fluid, namely the molten CMAS phase and the air phase; the model boundary was fixed, the initial CMAS concentration on the upper surface was 1 [that is, the upper surface was completely attached with CMAS in the initial stage, and the volume fraction was 1 (100%)], and the initial CMAS concentration on the lower surface was 0. The surface tension of the molten CMAS was 0.4 N / m and the density was 2630 kg / m 3 , viscosity is 15 Pa·s, and the CMAS concentration on all external surfaces of the model is 0; a transient study is set with an output step size of 0.01 s.
[0108] Among them, the physical quantities related to the physical properties of molten CMAS in this method, such as viscosity and surface tension, are all known quantities. The physical quantities such as model height, contact angle, effective radius of permeable pores, porosity, and permeability are calculated based on the numerical model established based on the microstructure. By introducing the constitutive equation established in formula (4) into COMSOL Multiphysics, the influence of the internal microstructure of the coating on the penetration behavior of CMAS can be obtained. According to the simulation results at different times, whether different areas inside the model are penetrated by CMAS, the average penetration depth change of CMAS in the model at different times can be obtained.
[0109] S6: Calculate and post-process the results to obtain the CMAS penetration behavior inside the microstructure of the thermal barrier coating (i.e., the penetration area and penetration depth changes of the molten CMAS inside the model at different times).
[0110] Substitute the established constitutive equation into the simulation software, and after the calculation is completed, the permeability of different areas inside the model at different CMAS penetration times is obtained. Figure 4 The penetration process of molten CMAS inside the microstructure of the thermal barrier coating shown in A, the red area is the part where the molten CMAS has penetrated, and the blue area is the part where the molten CMAS has not penetrated. It can be found that according to the model established by the coating provided in Example 1, the interior of the model is almost completely filled with molten CMAS after 3 seconds of penetration. In addition, it can be noted that when the penetration is in progress, the molten CMAS first penetrates the flow area with a larger pore radius, low tortuosity and no obstruction of unmelted particles.
[0111] Among them, according to Figure 4 The penetration depth of the model in A is changed, and the penetration depth (ordinate) of the CMAS penetration front is collected. The criterion for determining the CMAS penetration front is Figure 4 The critical position of the change in CMAS volume fraction in the calculation result shown in A (the critical point where the volume fraction changes from 1 to <1). Then, a point is collected every 1 micron in the horizontal direction, and the vertical coordinates of 15 points are obtained and averaged, which is the average penetration depth at each penetration time point.
[0112] According to the calculation results, we can get Figure 5 The average penetration depth change within 3 seconds of penetration in the microstructure of the thermal barrier coating shown in the figure shows that the increase rate of the average penetration depth gradually slows down with the extension of the penetration time, and the average penetration depth of the thermal barrier coating sample in Example 1 after 3 seconds of penetration by molten CMAS is 9.6 μm.
[0113] Example 2
[0114] The specific steps of the method for predicting the penetration behavior of molten CMAS of thermal barrier coatings involved in Example 2 are the same as those in Example 1, and the difference from Example 1 is that Example 2 provides thermal barrier coating samples with different microstructures. The main spraying parameters in step S1 are current 500A, power 35kW, main gas Ar flow rate 35SLPM, H2 flow rate 6SLPM, spraying distance 100mm, spray gun speed 500mm / s, coating composition 8wt% Y2O3-ZrO2, and the thickness of the obtained YSZ coating is about 900μm.
[0115] The obtained coating samples were extracted by scanning electron microscopy. Figure 2 The microstructural features of the coating shown in DE. Accordingly, the numerical model established in step S2 Figure 2 As shown in F, the white part is the unmelted particles and the black part is the infiltration pores. After step S3, the Figure 3 B shows the result of model meshing.
[0116] Subsequently, the infiltration conditions of different areas within the model at different CMAS infiltration times were obtained according to steps S4-S6 (e.g. Figure 4 B). It can be found that according to the model established by the coating provided in Example 2, there are still a large number of areas at the lower end of the model that are not filled by the molten CMAS after 3 seconds of penetration.
[0117] According to the calculation method provided in Example 1, it can be known that the average penetration depth of the thermal barrier coating sample in Example 2 after the molten CMAS penetrates for 3 seconds is 6.4 μm ( Figure 5 shown).
[0118] Actual experiment: Figure 6 As shown, the actual penetration depth of the thermal barrier coating samples prepared in step S1 of Example 1 and Example 2 after CMAS penetration for 1 hour was measured using molten CMAS of the same composition, viscosity, density, and surface tension. The composition of the CMAS powder used in the actual experiment is 45SiO2-33CaO-13AlO 1.5 -9MgO (mol.%).
[0119] according to Figure 6 The image contrast difference in AB can be used to determine that the penetration front depths of the actual thermal barrier coating samples in Example 1 and Example 2 are approximately 220 μm and 187 μm respectively after CMAS penetration for 1 hour. Therefore, the method provided by the present invention can effectively predict the CMAS penetration behavior of the thermal barrier coating based on its microstructural characteristics.
[0120] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the claims of this patent application.
Claims
1. A method for predicting the penetration behavior of molten CMAS of zirconia-based thermal barrier coatings, characterized in that: The following steps are involved: S1: Prepare thermal barrier coating and obtain microstructure image of thermal barrier coating using scanning electron microscope; S2: Use MATLAB image processing to build a numerical model based on the microstructure image of the thermal barrier coating; S3: Mesh the established numerical model in COMSOL Multiphysics; S4: Based on the Carman-Kozeny model and Darcy's law, a constitutive equation reflecting the relationship between the molten CMAS penetration time, porosity, penetration path complexity and penetration contact angle inside the coating is established; S5: Select the physical field interface, bring the constitutive equation into COMSOL Multiphysics, set the parameters and boundary conditions for calculation; S6: Post-process the calculation results to obtain the CMAS penetration behavior inside the microstructure of the thermal barrier coating.
2. The prediction method according to claim 1, characterized in that: In step S1, the method for preparing the thermal barrier coating is: plasma spraying, electron beam physical vapor deposition or plasma spraying-physical vapor deposition.
3. The prediction method according to claim 1, characterized in that: In step S2, MATLAB image processing is used to determine the threshold of the microstructure image of the thermal barrier coating through a gray threshold function, and the im2bw function is used to convert the microstructure image of the thermal barrier coating into a threshold-based binary image. The imerode and imexpate functions are used to eliminate the noise in the binary image, and finally the processed binary image is converted into a vector image to complete the modeling.
4. The prediction method according to claim 1, characterized in that: In step S3, the physical field in COMSOL Multiphysics is used to control the mesh, the unit type is a free triangle mesh, the maximum mesh size is 0.2 μm, the minimum mesh size is 0.004 μm, and an adaptive mesh is used to simulate the CMAS penetration process.
5. The prediction method according to claim 1, characterized in that: The specific method of step S4 is: (1) Based on Darcy's law, a relationship between the penetration time of molten CMAS is established; (2) establishing a relationship for the effective radius of the CMAS permeable pore based on the numerical model established in step S3; (3) Based on the Carman-Kozeny model, the relationship between CMAS permeability and the internal microstructure of thermal barrier coatings is established; (4) Combining steps (1)-(3), a constitutive equation for the relationship between the molten CMAS penetration time, porosity, penetration path complexity and penetration contact angle inside the coating is established.
6. The prediction method according to claim 5, characterized in that: The relationship between the penetration time of molten CMAS and the time of molten CMAS is: Wherein, t is the penetration time of molten CMAS, s; r is the effective radius of the CMAS penetration pore, μm; μ is the viscosity of molten CMAS, Pa·s; x is the model height, μm; σ is the surface tension of molten CMAS, N / m; θ is the contact angle between molten CMAS and the model, °; k is the permeability of CMAS in the model, μm 2 .
7. The prediction method according to claim 6, characterized in that: The relationship between the effective radius of the CMAS permeable pore is: Where b is the equivalent radius of the model, μm; a is the equivalent radius of the unmelted particles in the model, μm.
8. The prediction method according to claim 7, characterized in that: The relationship between CMAS permeability and the internal microstructure of thermal barrier coating is: Where k is the CMAS permeability in the model, μm 2 ; φ is the porosity, %; τ is the geometric shape factor, which is used to describe the complexity of the penetration path, which is equal to the effective area of the penetration pores / the effective area of the unmelted particles.
9. The prediction method according to claim 8, characterized in that: The constitutive equation of the relationship between the penetration time, porosity, complexity of the penetration path and the penetration contact angle of the molten CMAS inside the coating is:
10. The prediction method according to claim 1, characterized in that: In step S5, the phase field and laminar flow interfaces are selected for COMSOL simulation, the model boundary is fixed, the initial CMAS concentration of the upper surface is 1, the initial CMAS concentration of the lower surface is 0, and the CMAS concentration of all external surfaces of the model is 0; Set up a transient study with an output step size of 0.01 seconds; In step S6, the CMAS penetration behavior includes: the penetration area and penetration depth changes of the molten CMAS inside the model at different times.
Citation Information
Cited By
Knowledge-based distillation thermal barrier coating life prediction method and experimental optimization method
CN122455198A
Knowledge-based distillation method for predicting the lifetime of thermal barrier coatings and its experimental optimization.
CN122455198B